Unveiling the Sacred Journey: The Birth of a Woodblock-Printed Buddhist Canon in the Great Hangzhou Region of the Southern Song Dynasty - Li, Zhouyuan (Religions, 2023)
This article delves into the literature sources and historical origins of the initial section of the Qisha Canon, a renowned block-printed Chinese Buddhist Canon carved in the greater Hangzhou region during the Song and Yuan dynasties. The existing first twelve volumes, preserved in Japan, exhibit distinct features characterized by notable stylistic script, textual content, and layout. These features indicate their direct lineage from handwritten Buddhist canons of the Northern Song Dynasty rather than from previously printed versions. The utilization of handwritten sources as the foundation for engraving, despite the availability of established printed editions, demonstrates an underappreciated complex relationship between manuscripts and printed canons of the period. Throughout the engraving process of the twelve volumes, the majority of contributors were found to be local commoners, with minimal participation from Buddhist followers. The fluidity of the fundraising locations underscores the inherent instability of such projects. Initially commencing in Liaoqin’s hometown in Huzhou, the project was subsequently transferred to the imperial city of Lin’an prefecture (modern Hangzhou), which shared a border with Huzhou. Ultimately, it found its new location in Pingjiang Prefecture (modern Suzhou). Moreover, this research presents a comprehensive analysis of 195 colophons, delving into the prices, locations, and backgrounds of the characters mentioned. This meticulous examination offers a vivid depiction of the religious and social landscape of the period and provides valuable insights into the recording conventions employed in these colophons.